Clinical efficacy of transrectal ultrasound‐guided prostate biopsy in men younger than 50 years old with an elevated prostate‐specific antigen concentration (>4.0 ng/mL). Issue 7 (July 2017) - Lu, Chin‐Heng; Lin, Tzu‐Ping; Shen, She Huei; Huang, Yi‐Hsiu; Chung, Hsiao‐Jen; Kuo, Junne‐Yih; Huang, William J.S.; Wu, Howard H.H.; Chang, Yen‐Hwa; Lin, Alex T.L.; Chen, Kuang‐Kuo
Abstract : Background : Prostate cancer (PCa) is not commonly found in men younger than 50 years of age. However, serum prostate‐specific antigen (PSA) concentration has been examined more frequently at a younger age in Asia partially due to an increased awareness of prostate cancer. The purpose of our study was to investigate the efficacy and complication of PSA‐triggered transrectal ultrasonography‐guided prostate (TRUSP) biopsies. We retrospectively reviewed TRUSP biopsies in young men with elevated PSA concentration in Taipei Veterans General Hospital. Methods : We reviewed the cases of patients younger than 50 years of age with elevated PSA concentration (>4.0 ng/mL), who received 12 cores TRUSP biopsies at TPEVGH from January 2008–December 2013. The age, family history, digital rectal examination (DRE) results, PSA concentration, free/total PSA ratio, total prostate volume, PSA density, lower urinary tract symptoms and complications after the procedure were reviewed. The pathologic findings of TRUSP biopsy and clinical follow‐up were reviewed and analyzed according to the Epstein criteria. Results : A total of 77 patients were included and were divided into 2 groups: 1) the younger group consisted of 20 patients <40 years of age; and 2) the elder group had 57 patients who were 40–50 years of age. The overall detection rate of PCa was 11.69% (9/77), and all of the PCa cases were diagnosed in the elder group (group detection rate: 15.8%). There was a significant difference in the severity of lower urinary tract symptoms (LUTS) between these 2 groups. All PCa patients were clinically significant according to the Epstein criteria. Two patients experienced fever (2.60%) after TRUSP biopsy. Conclusion : From our patient cohort, it appears that no benefit was apparent for patients younger than 40 years old who received TRUSP biopsy, even with elevated PSA. However, PCa detected in men between 40 and 50 years of age were all clinically significant. Overall, our results supported current major practice guidelines which recommend an initial PSA checkup at 40 years of age.